2021
DOI: 10.1177/09500170211059420
|View full text |Cite
|
Sign up to set email alerts
|

China and the Internationalisation of the Sociology of Contemporary Work and Employment

Abstract: The China e-Special Issue brings together 11 articles on the sociology of contemporary work and employment in China which have been published in WES in the past two decades, highlighting the increasing frequency of submissions, and also reflecting the diversity, complexity and plurality of work and employment in the region. The foci of debates include the changing fault lines of work and employment; the changing relationships between state, employers and workers; the impact of rural to urban migration and urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…High-tech firms in China construct their corporate cultures in a distinctive historical, political and economic context. The BRI and the nationwide 'Chinese Dream' propaganda have marked a new stage of the reform era, when national renaissance has become the spirit of the CCP's political narrative (Kofman et al, 2021). The massive layoffs and problematic managerial practices in the high-tech industry, in particular the '996 work schedule' and the subsequent online 996.ICU movement (Li, 2019) have shown that the social contract between employment security and loyalty and commitment has irreversibly changed.…”
Section: A New Context Of Corporate Culture Building In China's High-...mentioning
confidence: 99%
See 3 more Smart Citations
“…High-tech firms in China construct their corporate cultures in a distinctive historical, political and economic context. The BRI and the nationwide 'Chinese Dream' propaganda have marked a new stage of the reform era, when national renaissance has become the spirit of the CCP's political narrative (Kofman et al, 2021). The massive layoffs and problematic managerial practices in the high-tech industry, in particular the '996 work schedule' and the subsequent online 996.ICU movement (Li, 2019) have shown that the social contract between employment security and loyalty and commitment has irreversibly changed.…”
Section: A New Context Of Corporate Culture Building In China's High-...mentioning
confidence: 99%
“…This article offers an updated analytical lens by theorising a divergent formation of corporate culture in China's tech sector contextualised in a specific state-employeremployee relation, contrasting and complementing key research in this area (Davies, 2007;Hawes, 2008;Hawes and Chew, 2011;Huang, 2008;Kunda, 2006;Lai et al, 2020). The recent Belt and Road Initiative (BRI) and the nationwide 'Chinese Dream' propaganda have marked a new stage of the reform in China when national renaissance has become the zeitgeist of the Chinese Communist Party's (CCP) political narrative (Kofman et al, 2021). More specifically, seeking to become a great global power, the CCP has developed new national discourse of revitalisation through technological development, 'indigenous innovation' and soft power building since 2012 (Publicity Department of the CPC Central Committee [PD], 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the professional and social lives of Hong Kong creative workers were selected as an ideal situated field for theorising how divergent external structural and contextual factors (e.g. Alberti et al, 2018; Gallie et al, 2017; Kofman et al, 2021; Tomlinson et al, 2018) intersect and co-configure their varying insecurity perceptions, experiences, responses and coping mechanisms . It was designed to challenge ‘the current epistemological ethnocentrism of creative labour studies’ (Alacovska and Gill, 2019: 205), refine overgeneralised ‘Northern’ theoretical claims about how work insecurities in the creative industries are generated and experienced (Gill and Pratt, 2008; Hesmondhalgh and Baker, 2010, 2011) ‘ground a more realistic and complex understanding of creative labour within the political economy of particular creative industries’ (Thompson et al, 2015: 327), and yield a pluralistic epistemology of the ‘concrete struggles fighting precarity inside and outside the workplace’ (Alberti et al, 2018: 454).…”
Section: Introductionmentioning
confidence: 99%